Influence of Au doping on electrical properties of CVD graphene. (April 2016) - Krajewska, Aleksandra; Oberda, Krzysztof; Azpeitia, Jon; Gutierrez, Alejandro; Pasternak, Iwona; López, Maria F.; Mierczyk, Zygmunt; Munuera, Carmen; Strupinski, Wlodek
Abstract: In this study we report on the effective p-doping of chemical vapor deposition (CVD) graphene transferred from copper foil onto SiO2 /Si and PET substrates. Tetrachloroauric acid (HAuCl4 ) is used to promote graphene doping with a direct correlation between its concentration and modification of graphene's electrical properties. The doping mechanism entails the charge transfer (CT) between Au III ions and graphene, and the formation of Au nanoparticles (AuNPs) on the surface. X-ray photoelectron spectroscopy (XPS) was employed to confirm this charge transfer, whereas the presence of the AuNPs was verified based on Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) images. The influence of doping on the electrical properties of graphene was assessed by Kelvin Probe Microscopy (KPM) and standard Hall Effect measurements, proving the ability of the method to effectively tune the carrier concentration, achieving sheet resistances as low as 79 Ω/sq. The controlled tuning of the electrical properties together with the use of flexible substrates makes the presented results a very interesting approach enabling the development of a variety of industrial applications, including flexible electronics.